Initiation Ceremony in Primitive Tribes and Some Religions - Necati Sümer (Dini Araştırmalar)

(untitled)
Initiation ceromony is a ritual that signifies when someone reach to a certain age then,an attempt to be a member of an assembly or a group. This initiation ceromony can be occured in any society either in a primitive or in a civilized society. Although, the implementationsprocess of initiation ceromony may sometimes vary however the purpose of it remains same. This is the purpose make individuals to accustom to the collective educational, religious or mithic sense. In preliterate society these rituals are loaded with religious content. In primitive societies the initiation ceremony were also held when the young girls and boys reach their puberty age and also when they are seen as an adult of the society. The ceremony contains some difficult ordeals for the youngs and in order to become successful participant to gain admittance to the society these young people need to prove themselves through these difficult ordeals. In some primitive societies gaining admittance and becoming a member require that getting intercourse with his protective spirit. At the end of all these process, the candidate gains a name and full membership when if succesfully complete the tasks and they become adults who now have social affiliation. These rituals can also be observed in civilized society’s culture. The initiation ceremony in advanced societies’ religious traditions is however different and the rituals are contain more symbolic meanings. The principal of physical suffering during initiation ceremonies in primitive society is the form of spiritual readiness in civilized societies. Hindu Upanayana, Jewish Bar/Bat Mitzvah and baptism rituals of Christians are typical ceremonies initiation. This study examines how the initiation ceremony that an important social ritual, takes place in the religious tradition of primitive and some civilized societies.